2021
DOI: 10.1093/nar/gkab984
|View full text |Cite
|
Sign up to set email alerts
|

MicroDNA levels are dependent on MMEJ, repressed by c-NHEJ pathway, and stimulated by DNA damage

Abstract: Extrachromosomal circular DNA (eccDNA) are present within all eukaryotic organisms and actively contribute to gene expression changes. MicroDNA (200-1000bp) are the most abundant type of eccDNA and can amplify tRNA, microRNA, and novel si-like RNA sequences. Due to the heterogeneity of microDNA and the limited technology to directly quantify circular DNA molecules, the specific DNA repair pathways that contribute to microDNA formation have not been fully elucidated. Using a sensitive and quantitative assay tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 53 publications
4
41
1
Order By: Relevance
“…They often involve damage to the chromosomal DNA and erroneous actions by different DNA repair pathways. For example, two double-strand breaks (DSBs) in the same chromosome can result in a stretch of DNA deleted, which could become circularized (Figure 1A), or secondary DNA loop structures formed in several processes, for example, mismatch repair (MMR) (see Glossary), could be excised and circularized [35][36][37]. Therefore, the mechanisms for eccDNA formation can be different depending on how and where chromatin is subjected to damage and which DNA repair mechanisms are active in a given cell.…”
Section: Formation and Maintenancementioning
confidence: 99%
See 2 more Smart Citations
“…They often involve damage to the chromosomal DNA and erroneous actions by different DNA repair pathways. For example, two double-strand breaks (DSBs) in the same chromosome can result in a stretch of DNA deleted, which could become circularized (Figure 1A), or secondary DNA loop structures formed in several processes, for example, mismatch repair (MMR) (see Glossary), could be excised and circularized [35][36][37]. Therefore, the mechanisms for eccDNA formation can be different depending on how and where chromatin is subjected to damage and which DNA repair mechanisms are active in a given cell.…”
Section: Formation and Maintenancementioning
confidence: 99%
“…shown to result in a decreased amount of eccDNA in chicken lymphoma and human cancer cells [35,37]. In the most recent of these, deficiency of genes involved in damaged DNA resection and microhomology-mediated end joining (MMEJ) also resulted in decreased eccDNA amounts [37].…”
Section: Trends In Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above studies indicated that the DNA damage repairing pathways including homologous recombination (HR) or nonhomologous end-joining (NHEJ) and microhomology-mediated end-joining (MMEJ) are involved in the formation of microDNAs ( Dillon et al, 2015 ; Paulsen et al, 2021 ). The cells lack 53BP1 and XRCC4 promoting the canonical-NHEJ (c-NHEJ), resulting in more microDNA.…”
Section: The Biogenesis Of Eccdnamentioning
confidence: 99%
“…The cells lack 53BP1 and XRCC4 promoting the canonical-NHEJ (c-NHEJ), resulting in more microDNA. On the contrary, the deficiency of NBS1, POLQ, RAD54, MLH1, MSH2, MSH3, FAN1, and NBS results in the decrease of microDNA ( Paulsen et al, 2021 ). The short, reverted repeats at both ends of junction sites provide perfect places to initialize homologous recombination (HR) during eccDNA formation.…”
Section: The Biogenesis Of Eccdnamentioning
confidence: 99%